Análise de moléculas envolvidas no metabolismo de nitrogênio no fungo patogênico humano Paracoccidioides brasiliensis - Silva, Lana OHara Souza (2017)
The Paracoccidioides genus is composed of thermodimorphic fungus that causes paracoccidioidomycosis (PCM), an endemic human systemic mycosis in Latin America. These organisms grow as mycelium in temperatures below 28 °C and as yeast form in temperatures above 37 °C. Nitrogen is an important element in this microorganism’s nutrition that participates in the synthesis of proteins, nucleic acids and others biomolecules. In this regard, nitrogen uptake and metabolism are essential to growth and fungal establishment. When nitrogen levels and sources such as glutamine and ammonia concentration are limited, pathogenic fungus use a regulation system called Nitrogen Catabolic Repression that induces the expression of genes encoding permeases and enzymes required for the catabolism of secondary nitrogen sources, such as formamidase, gamma-glutamiltranspeptidase and urease. Gamma-glutamiltranspeptidase is an enzyme that catalyzes the first reaction of glutationa degradation and it has been the target of several studies about nitrogen starvation in various fungi. It has been observed that the expression of the gene encoding this enzyme was induced in limiting conditions of nitrogen and was repressed when the availability of nitrogen was high. Urease is an enzyme that catalyzes the degradation of urea in ammonia and carbonic acid. This enzyme is already known as a virulence factor in fungi such as Cryptococcus. neoformans, and also has been the target of studies about nitrogen starvation. In this study we expressed gamma-GT and urease proteins from Paracoccidioides brasiliensis, isolate Pb18, in Escherichia coli. The gene coding for Ggt and Ure were cloned in pET32a expression vector, and used for E. coli pLysS transformation. The recombinant proteins produced were shown to be catalytically active. Together, data obtained in this work could add knowledge about the role of gamma-GT and urease and can be used as a foundation for complementary experiments regarding nitrogen metabolism regulation, as well as in Paracoccidioides spp pathogenesis.